Assessing professional skills in engineering education - Cajander, Å.; Daniels, M.; McDermott, R.; Von Konsky, Brian (Australian Computer Society, 2011)
This paper addresses the issue of developing and assessing professional skills in higher education programs. This includes defining and assessing these skills, in the contexts of an individual course unit and for an entire degree program. Identifying forms of assessment that are seen as authentic, meaningful and understandable by the students, teaching staff and curriculum developers are of utmost importance if professional skills are to be accepted and included in the formal curriculum. This can be particularly important in programs that aim to offer students a truly collaborative learning experience in a culturally diverse team. Reflections are presented as one example of an assessment method that fits this requirement. Building assessment based on the notion of threshold concepts is introduced in the context of an open ended group project course unit at Uppsala University.